Needs Analysis of Cyber Education-Based Pre-Marriage Guidance Models for Students - Faridati Zen, Ella; Nikmah Puspitasari, Dwi; Multisari, Widya; Probowati, Devy; binti Sulaiman, Hamidah (KnE Social Sciences, 2022)
Marriage is a task of individual development. Conflicts, problems, and mismatches of expectations must be faced in marriage. Couples who are unable to resolve these issues will be more likely to choose separation or divorce. There are high divorce rates in Indonesia. Pre-marital guidance is part of efforts to prepare prospective married couples to achieve the expected quality of marriage. Currently, pre-marital guidance is carried out conventionally, such as through seminars or training. Meanwhile, what is needed by today’s Millennial society is clear, accurate, and flexible information to be accessed anywhere and anytime. For this reason, efforts are needed to develop a cyber education-based pre-marital guidance service model. The purpose of this study was to provide an analysis of material needs for the Cyber Education-Based Pre-Marriage Guidance Model. Descriptive quantitative methodology was used and data were collected through a Google Forms questionnaire. This questionnaire consisted of 18 questions compiled with the aim of uncovering needs relating to the following: 1) formulation of problems; 2) determination of the type of information or data; 3) data collection procedures; 4) data processing; and 5) decision-making based on data analysis results. 280 students from LPTK universities throughout Java participated, including from Universitas Negeri Malang, Universitas Negeri Surabaya, Universitas Negeri Semarang, Universitas Negeri Yogyakarta, and Universitas Pendidikan Indonesia. Keywords: pre-wedding guidance, cyber education, students